Risk factors of chronic noncommunicable diseases comorbidity in South-Kazakhstan region - Saule Urazalina; Aisulu Musagalieva; Assel Issabekova; Kulzida Koshumbayeva; Bagdat Akhit (National Scientific Medical Center, 2019)
Aim: To conduct a one-stage multicenter study in South-Kazakhstan Region to obtain baseline prevalence of comorbidity of chronic noninfectious diseases and their risk factors. Material and methods: 1400 persons at the age of 18-69, living in the South-Kazakhstan region. Epidemiological part consisted of: interviewing, physical examination and laboratory tests. For statistical analysis were used MSAccess and SPSS22.0. computer programs. Results: 12.7% of respondents in South-Kazakhstan region smoke, which statistically significantly less than number of nonsmoking (87.3%; p<0.01) ones. The number of alcohol drinkers is 28.4%, which also less than number of nondrinkers (71.6%; p<0.01). The 48.3% of people included in the study had physical inactivity, while 51.7% had sufficient physical activity. More than half of respondents had abdominal obesity (67.9%), which higher than number of people without obesity (32.1%; p<0.01). The 72.1% had chronic noninfectious diseases (1009 of 1400). Comorbidity with two diseases - 48.2% (676 of 1400). Most common disease was arterial hypertension (45.9%: 464 of 1009). Less common - chronic kidney disease (2.4%:24 of 1009). The most common comorbidity - arterial hypertension and diabetes mellitus (72.3%). The less common - obesity and chronic obstructive pulmonary diseases (2.3%). Conclusions: 1. The most common risk factors of chronic noninfectious diseases in South-Kazakhstan region are improper diet, obesity, physical inactivity. 2. The frequency of chronic noninfectious diseases in South-Kazakhstan region was 72.1%. And the most common disease was arterial hypertension. 3. The most common comorbidity - combination diabetes mellitus with arterial hypertension while the less common - combination obesity with chronic obstructive pulmonary disease.